2010
DOI: 10.1002/art.27763
|View full text |Cite
|
Sign up to set email alerts
|

Improved outcome in 445 patients with Wegener's granulomatosis in a German vasculitis center over four decades

Abstract: Objective. To determine the long-term outcome in patients with Wegener's granulomatosis (WG) over 4 decades in an academic hospital unit specializing in rheumatology.Methods. We included 290 patients, divided them into 2 cohorts, and compared them with the historical cohort of 155 patients. Comparisons were retrospective regarding disease manifestations, therapy, mortality, and incidence of malignancies. The historical cohort (cohort 1) included 155 patients diagnosed between 1966 and 1993, cohort 2 included 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
144
7
29

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 251 publications
(192 citation statements)
references
References 36 publications
12
144
7
29
Order By: Relevance
“…[11][12][13]15 ANCA was negative in 10% of patients in our study, which is similar to that reported from other studies, where ANCA negativity ranged from 10 to 13%. [4][5][6][7][8] Renal involvement was seen in fewer patients in our study population compared to studies from Europe, America and also older studies from India. The more recent Indian study by Kumar et al has also shown that renal involvement is seen in 33% of patients in their cohort.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…[11][12][13]15 ANCA was negative in 10% of patients in our study, which is similar to that reported from other studies, where ANCA negativity ranged from 10 to 13%. [4][5][6][7][8] Renal involvement was seen in fewer patients in our study population compared to studies from Europe, America and also older studies from India. The more recent Indian study by Kumar et al has also shown that renal involvement is seen in 33% of patients in their cohort.…”
Section: Discussioncontrasting
confidence: 50%
“…GPA seems to affect a relatively younger population in India compared to European and American populations, as the mean age of presentation in our subjects is 40 years which is about a decade earlier than in European and American populations. [4][5][6][7][8] Older Indian studies have noted the mean age of presentation to be between 32 to 42 years, but a recent study documented a mean age of 46 years, which is comparable to that of Western studies. [11][12][13]15 ANCA was negative in 10% of patients in our study, which is similar to that reported from other studies, where ANCA negativity ranged from 10 to 13%.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Dementsprechend ist die Akkumulation von Erfahrung in der Diagnostik und Therapie der AAV an die Konzentration dieser Patienten in Zentren gebunden. Mono-und multizentrische Kohorten belegen eine kontinuierliche Verbesserung der Prognose quo ad vitam [93,192,248]. In jüngerer Zeit konnte eine Lebenserwartung, die sich nicht signifikant von der der Allgemeinbevöl-kerung unterschied, bei einem Großteil der AAV-Patienten unter Behandlung durch spezialisierte Zentren erreicht und nachgewiesen werden [93,164,205].…”
Section: üBergeordnete Empfehlungen üBergeordnete Empfehlungunclassified
“…Mono-und multizentrische Kohorten belegen eine kontinuierliche Verbesserung der Prognose quo ad vitam [93,192,248]. In jüngerer Zeit konnte eine Lebenserwartung, die sich nicht signifikant von der der Allgemeinbevöl-kerung unterschied, bei einem Großteil der AAV-Patienten unter Behandlung durch spezialisierte Zentren erreicht und nachgewiesen werden [93,164,205]. Aus vergleichbaren Zeiträumen und unter ähnlichen (teils jedoch älteren) Therapiestandards gewonnene Daten zeigen ebenso wie historische Daten bei dezentraler Behandlung eine nach wie vor gesteigerte Mortalität gegenüber der Normalbevölkerung [1,53,55,146].…”
Section: üBergeordnete Empfehlungen üBergeordnete Empfehlungunclassified